Kombinasi Massage Nape dan Teknik Marmet terhadap Percepatan Pengeluaran ASI pada Ibu Post Partum - Endah Tri Wahyuni; Ratna Wulan Purnami (Politeknik Kesehatan Tanjung Karang, 2020)
WHO in 2016 still shows the average rate of exclusive breastfeeding (ASI) in the new world is around 38%. In Indonesia, although a large number of women (96%) breastfeed their children in their lifetime, only 42% of babies under 6 months of age are exclusively breastfed. By the time children approach their second birthday, only 55% are still being breastfed. When compared with the WHO target of 50%, this figure is still far from the target. Maximum achievement can be applied by applying nape and marmot massage techniques for postpartum mothers so that breast milk can be released more quickly. This study aims to help and explain the combination of nape and marmet massage techniques to speed up the use of breast milk in postpartum mothers in the working area of Ngaglik II Sleman Health Center. This research is Quasi-Experimental research using quantitative and post-test designs, with a sample of 30 respondents divided into groups given intervention and control groups taken by purposive sampling. Univariate and bivariate data analysis. The results showed that the effect of nape massage combination and guinea pig technique on the acceleration of ASI use based on the Mann Whitney Test statistical test showed results (p-value 0,002)<0,05. The combination of nape massage and marmet technique has an effect on accelerating breastfeeding.